Hubungan Antara Stres Psikis Menjelang UAN dan SNMPTN dengan Kejadian Fluor Albus pada Siswi SMA Peserta Bimbingan Belajar - Jeanne Fransisca; Yoseph Indrayanto; Slamet Riyadi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: The incidence number of psychological stress before UAN and SNMPTN in XII grade of high school students is quite high. This is so adverse because psychological stress itself could affect students health. For example, psychological stress could be a cause of whitish or fluor albus in female students. If this is ignored, it would be dangerous. For those reasons, this research was done to reveal the relation between psychological stress before UAN and SNMPTN to fluor albus incidence in female high school study course participants. Methods: The method of this research was analytical observation with cross sectional approach. The subject was female high school students grade XII and participants of study course in Surakarta. Author used purposive sampling as sampling technique and to gather the data author usedLie-Minnesota Multiphasic Personality Inventory (L-MMPI) questionnaires, anxiety facing UAN and SNMPTN questionnaires, DASS42 questionnaires, and fluor albus incidence questionnaires. Data were collected from 60 samples and was analyzed by Chi Square (X2) test and Coefficient Continquency (CC. Results: From this research, author obtained X2 score value(5,406) is bigger than X2 tablevalue (3,841) with signification rate (?) = 0,05 and independence degree (df) = 1. As for the p value obtained (0,02) is smaller than the significance level which is already defined previously (0,05). Those were shown that H0 was rejected. Data analysis was continue to Coefisien Continquency (CC) test which then obtained the value of CC = 0,287. It means that the relation is weak. Conclusion: There was a weak relation statistically between psychological stress before national examination (UAN) and national university entrance examination (SNMPTN) to fluor albus incidence in female high school study course participants. Keywords: Psychological Stress, UAN, SNMPTN, Fluor Albus